2018
DOI: 10.1007/s00134-018-5308-4
|View full text |Cite
|
Sign up to set email alerts
|

Intensive care support and clinical outcomes of patients with Ebola virus disease (EVD) in West Africa

Abstract: PurposeWe investigate the impact on outcome of different levels of supportive treatment in Ebola virus disease (EVD). The NGO EMERGENCY delivered care sequentially at two Ebola Treatment Centres (ETC) in Sierra Leone: first at Lakka (fluids, symptomatic, antibiotic, antimalaria treatment, and hospital level medical care), and thereafter in Goderich, adding organ support in the only African ETC with an equipped and staffed intensive care unit (ETC-ICU).MethodsThe primary outcome in this retrospective cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
(24 reference statements)
0
16
0
Order By: Relevance
“…The observations of temporary fluid and vasoactive medication responsiveness may shed light on a recent report that demonstrated that while generally ineffective during the West African outbreak, a subset of patients, with a moderate viral load, benefited from ICU-type supportive care [27]. We hypothesize that responsiveness to supportive care may enable patients with moderate disease to survive long enough for immune responses to control the infection.…”
Section: Discussionmentioning
confidence: 81%
“…The observations of temporary fluid and vasoactive medication responsiveness may shed light on a recent report that demonstrated that while generally ineffective during the West African outbreak, a subset of patients, with a moderate viral load, benefited from ICU-type supportive care [27]. We hypothesize that responsiveness to supportive care may enable patients with moderate disease to survive long enough for immune responses to control the infection.…”
Section: Discussionmentioning
confidence: 81%
“…However, given the resource constraints typical of most outbreak areas, the capacity to deliver critical care is limited by gaps at the personnel, equipment and facility levels. The knowledge of modern critical care of patients with EVD stems from the care of several patients who acquired EBOV infection in Western Africa but were managed in the USA and Europe 140,175,[199][200][201][202] , and limited experience in an ETU in Sierra Leone that was equipped with intensive care unit (ICU) capabilities 203 . Substantial pre-planning was necessary to provide treatment for critically ill patients, to ensure the availability of physicians with experience in airway management and dialysis, for example, and the necessary equipment and appropriate PPE for potentially aerosol-generating procedures.…”
Section: Critical Carementioning
confidence: 99%
“…hospitals in high-income countries 2,[61][62] or settings in low and middle-income countries where high standard of care can be guaranteed). 63 At best this aRCT would be a part of an ongoing integrated intervention for infection control that also includes hospital-based surveillance of MDR bacteria and antimicrobial stewardship programmes. 64 The aRCT is expected to enroll complex patients potentially in need of multiple simultaneous empiric therapies.…”
Section: Ceftazidime/avibactam: An Overview Of Current Knowledge Frommentioning
confidence: 99%